MicroRNAs Associated With a Good Prognosis of Acute Myeloid Leukemia and Their Effect on Macrophage Polarization - Neaga, Alexandra; Bagacean, Cristina; Tempescul, Adrian; Jimbu, Laura; Mesaros, Oana; Blag, Cristina; Tomuleasa, Ciprian; Bocsan, Corina; Gaman, Mihaela; Zdrenghea, Mihnea (Frontiers in Immunology, 2021)
Acute myeloid leukemia (AML) is an aggressive myeloid malignancy with poor outcomes despite intensive therapeutic approaches. For the majority of patients which are unfit and treated less intensively, the prognosis is even worse. There has been unspectacular progress in outcome improvement over the last decades and the development of new approaches is of tremendous interest. The tumor microenvironment is credited with an important role in supporting cancer growth, including leukemogenesis. Macrophages are part of the tumor microenvironment and their contribution in this setting is increasingly being deciphered, these cells being credited with a tumor supporting role. Data on macrophage role and polarization in leukemia is scarce. MicroRNAs (miRNAs) have a role in the post-transcriptional regulation of gene expression, by impending translation and promoting degradation of messenger RNAs. They are important modulators of cellular pathways, playing major roles in normal hematopoietic differentiation. miRNA expression is significantly correlated with the prognosis of hematopoietic malignancies, including AML. Oncogenic miRNAs correlate with poor prognosis, while tumor suppressor miRNAs, which inhibit the expression of proto-oncogenes, are correlated with a favorable prognosis. miRNAs are proposed as biomarkers for diagnosis and prognosis and are regarded as therapeutic approaches in many cancers, including AML. miRNAs with epigenetic or modulatory activity, as well as with synergistic activity with chemotherapeutic agents, proved to be promising therapeutic targets in experimental, pre-clinical approaches. The clinical availability of emerging compounds with mimicking or suppressor activity provides the opportunity for future therapeutic targeting of miRNAs. The present paper is focusing on miRNAs which, according to current knowledge, favorably impact on AML outcomes, being regarded as tumor suppressors, and reviews their role in macrophage polarization. We are focusing on miRNA expression in the setting of AML, but data on correlations between miRNA expression and macrophage polarization is mostly coming from studies involving normal tissue.